2013
DOI: 10.3329/pa.v22i1-2.16479
|View full text |Cite
|
Sign up to set email alerts
|

Land Tenure System and Agricultural Productivity in a Selected Area of Bangladesh

Abstract: The relative efficiency of farming under tenancy systems in Bangladesh was measured in this study. Thirty cash tenants and 30 share tenants were randomly selected for data collection through field survey method from Narayanpur and Bhabokhali villages under Sadar upazila of Mymensingh district. The functional analysis of the study was based on Boro rice. The land tenancy situation in rural Bangladesh was explored in this study with a reasonable high incidence of owners who cultivate their own land in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…1). Nasrin and Uddin (2011) observed that a large number of sharing agreements under the pure share tenancy in Bangladesh mostly dependent on the proportion of cost sharing. Islam and Maharjan (2015) observed that in most of the cases the landowner takes 50 percent of the produced crops without sharing any portion of production costs and in less than 5 percent of the cases the sharing pattern was more than 50%.…”
Section: Patterns Of Crop Sharing Under the Tenancy Contractsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Nasrin and Uddin (2011) observed that a large number of sharing agreements under the pure share tenancy in Bangladesh mostly dependent on the proportion of cost sharing. Islam and Maharjan (2015) observed that in most of the cases the landowner takes 50 percent of the produced crops without sharing any portion of production costs and in less than 5 percent of the cases the sharing pattern was more than 50%.…”
Section: Patterns Of Crop Sharing Under the Tenancy Contractsmentioning
confidence: 99%
“…The existing sharing system is not always fairly balance the distribution of crop between tenants and landowners (Akanda et al, 2008;Zaman, 1973). Nasrin and Uddin (2011) concluded that the land tenancy structure significantly influences the use of inputs and production cost, which in turn affect the productivity. Banerjee et al (2002) found that relatively more land rights that lead to improved crop shares and higher security of tenure for tenants may have a positive effect on productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Land tenure agreements largely affect/influence the efficiency of farm inputs and the adoption of modern technologies, which in turn affect agricultural productivity. Keeping in view the scarcity of land and related resources, the distribution and tenure arrangements are regarded as key issues in the nation's development strategy (Nasrin and Uddin 2011). The term tenure connotes the bundle of rights an individual, household or community may have with respect to land or water or other resources for that matter (ibid).…”
Section: Introductionmentioning
confidence: 99%
“…FAO (1993) defines land tenure as the relationship (whether legally or customarily defined) among people, as individuals or groups, with respect to land. In simple words, land tenure systems determine the ownership (who can use what resource), time (for how long) and conditions of use of the land and related resources (Nasrin and Uddin 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The average farm size in Bangladesh is declining rapidly and land fragmentation is increasing [35] with 12.84% of households owning no land according to the 2008 census [26]. Average farm size declined from 0.81 ha in 1996 to 0.49 ha in 2005 [38]. Therefore, tenurial reform aimed at the smooth operation of the land-rental market along with effective implementation of the tenancy act will enable more households to enter farming as well as increase farm-operation size, which in turn will improve cattle-raising per household and contribute to supporting farming and milk and meat production.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%